Analysis of Farmers' Knowledge on Animal Feed Processing and Its Adoption Constraints: A Case Study - Gede Suarta; I Gusti Agung Nyoman Dananjaya; Novie Andri Setianto; Moh. Ihsan Zain (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
An effective animal feed extension program is expected to support the development of the livestock sector and improve farmers’ welfare. This study aims to analyze farmers’ knowledge of animal feed processing as an outcome of an extension program and to identify the constraints faced in adopting feed processing technologies. The research was conducted at the Putrayasa Livestock Farmer Group in Tenganan Village, Karangasem Regency, Bali, Indonesia. A census method was applied, involving all 54 group members as respondents. Data were collected through observation, interviews, and documentation, and analyzed using quantitative and qualitative descriptive approaches. The results show that farmers’ knowledge of animal feed processing is in the high category, with an average score of 4.06. This indicates that the extension program has been effective in improving farmers’ understanding of feed processing technologies. However, the adoption of these technologies remains limited. The main constraints identified include the inconsistent implementation of processed feed and financial limitations among farmers. These findings suggest that although extension programs are successful in increasing knowledge, additional efforts are required to enhance practical skills and address economic barriers to improve the adoption of feed processing technologies.